Wnt Signaling in Vascular Calcification - Bundy, Kaylee; Boone, Jada; Simpson, C. LaShan (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular disease is a worldwide epidemic and considered the leading cause of death globally. Due to its high mortality rates, it is imperative to study the underlying causes and mechanisms of the disease. Vascular calcification, or the buildup of hydroxyapatite within the arterial wall, is one of the greatest contributors to cardiovascular disease. Medial vascular calcification is a predictor of cardiovascular events such as, but not limited to, hypertension, stiffness, and even heart failure. Vascular smooth muscle cells (VSMCs), which line the arterial wall and function to maintain blood pressure, are hypothesized to undergo a phenotypic switch into bone-forming cells during calcification, mimicking the manner by which mesenchymal stem cells differentiate into osteoblast cells throughout osteogenesis. RunX2, a transcription factor necessary for osteoblast differentiation and a target gene of the Wnt signaling pathway, has also shown to be upregulated when calcification is present, implicating that the Wnt cascade may be a key player in the transdifferentiation of VSMCs. It is important to note that the phenotypic switch of VSMCs from a healthy, contractile state to a proliferative, synthetic state is necessary in response to the vascular injury surrounding calcification. The lingering question, however, is if VSMCs acquire this synthetic phenotype through the Wnt pathway, how and why does this signaling occur? This review seeks to highlight the potential role of the canonical Wnt signaling pathway within vascular calcification based on several studies and further discuss the Wnt ligands that specifically aid in VSMC transdifferentiation.